Interlocking directorship and firms performance: evidence from Malaysia / Wan Mohammad Taufik Wan Abdullah - Wan Abdullah, Wan Mohammad Taufik (2010)
This study was carried out to apply regression analysis in the prediction of corporate performance in Malaysia. Its focus is on one of the corporate governance issues which is on interlocking directorship. This study is to appraise whether the interlocking directorship and other factors like turnover, quick ratio and total debt to equity ratio can be good predictors for corporate performance. This study defines interlocking directorship as a situation where directors (executive or non-executive) sit on more than one board. There are top 100 companies listed under FTSE Bursa Malaysia Top 100 Index designated as samples in this study. Using two measures of corporate performance; earning per share (EPS) and return on equity (ROE). Two regression models have been developed in this study. Results show no significant relationship between both corporate performance measures EPS and ROE and interlocking directorship. This seems to suggest that the interlocking directorships in Malaysian firms have no implication on corporate performance. This might be due to the enforcement by Malaysia Code of Corporate Governance (MCCG) to all listed companies to form audit committee to monitor the board of directors independently. In addition, Bursa Malaysia Listing Requirement permits a director to hold up to 25 directorships at a one time, of which 10 directorships are in public listed companies and 15 directorships in unlisted companies.